Outcomes From Cytotoxic Chemotherapy Following Progression on Immunotherapy in Metastatic Melanoma: An Institutional Case-Series - Gaughan, Elizabeth M.; Horton, Bethany J. (Frontiers in Oncology, 2022)
INTRODUCTION: The role of chemotherapy in the management of advanced melanoma is limited due to low response rates and short survival. Improved outcomes to chemotherapy administered after immunotherapy for metastatic melanoma and other solid tumors have been reported. We studied the outcomes of subjects treated at the University of Virginia (UVA) with chemotherapy following progression on prior systemic immunotherapy and compared the results with the existing literature. MATERIALS AND METHODS: Subjects were identified through an institutional database of patients treated with immunotherapy at UVA. Demographic, pathologic and clinical factors were collected, along with dates of therapy, investigator-assessed best response as per Response Evaluation Criteria for Solid Tumors version 1.1 and dates of death or last follow up. Kaplan-Meier survival estimates and log-rank tests were used to perform time to event analysis of progression free survival and overall survival. RESULTS: Forty-five patients were identified who met the inclusion criteria including 24 men and 21 women with a median age of 61 years. All patients had received at least one line of immunotherapy including 64.4% with prior anti-PD1 treatment. The cytotoxic chemotherapy regimens used included carboplatin with paclitaxel (55.6%), temozolomide (31.1%) and nab-paclitaxel (13.3%). The overall response rate for cytotoxic chemotherapy 22.2% and the disease control rate was 35.6%. The median progression-free survival was 1.7 months and median overall survival was 4.7 months. Nineteen (42.2%) patients survived greater than 6 months and seven (15.5%) patients survived over 12 months. Fourteen patients were able to proceed to further therapy. DISCUSSION: Our results reveal that receipt of immunotherapy prior to chemotherapy for metastatic melanoma does not appear to improve the benefit of chemotherapy. The palliation of symptoms, maintenance of performance status and disease control may be valuable for some patients during this time of robust research and discovery for metastatic melanoma.